THE RELATIONSHIP BETWEEN MORPHOLOGICAL INDICATORS OF HUMAN BODY AND POSTURE - Molikova, Radka; Bezdickova, Marcela; Langova, Katerina; Holibka, Vladimir; David, Ondrej; Michalikova, Zdenka; Rehorova, Jarmila (Biomedical papers, 2006)
Background: Posture and Stability Control is a process of maintaining balance and position of the body and its parts in a constantly changing environment. It is an important regulatory mechanism of the body, because it precedes movement, is upon the completion of which this system tries to maintain the body position.Aim: The purpose of this long term study is to determinate by special testing which morphological indicators and how influence postural stability and its control.Method: This study used testing with NeuroCom Balance-12 protocols, anthropometric measuring - 32 values, anamnestic questionnaire. For this article we analyzed one chosen protocol: Weight Bearing Squat Test.Results: In this research, 41 individuals took part in it. 22 (53.66 %) were female, 19 (46.34 %) were male. Interesting statistically significant coherences were discovered during analysis of Weight Bearing Squat protocol on level p < 0.01, p < 0.05 and the Student's two-optional T-test proved statistically significantly higher values of Left Body Weight erect position and Left Body Weight 30° knee flexion in men in comparison with women.Conclusions: This study shows us a direction and we may consider it a convenient base for more specific continuation in this problematic area.
Keywords: Posture/Postural stability/Weight Bearing Squat/Body position/Morphological indicators/NeuroCom Balance